Assessment of hearing among mobile phone users - Kanagamuthu, Priya; Palanisamy, Thirunavukarasu; Srinivasan, Rajasekaran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: With the advent of new smart phones every day, health hazard related to it is also increasing. The usage of mobile phones has become a domineering activity of the students. Such usage have been documented to cause many health hazards like hearing loss, the mobile phone electromagnetic radiation has other potential risks like vehicular accidents, headache, and sleep disturbances, thermal effects and alteration of blood brain barrier. The objective of the study was to assess the hearing loss with pure tone audiometry due to chronic mobile phone usage among medical college students in a tertiary care hospital. Methods: This was a cross sectional study conducted among the medical students from June 2018 to December 2018, with the sample size of 129. The participants were interviewed using pretested, validated questionnaire followed the participants were subjected to pure tone audiometry. Results: Among the 129 participants, the majority of the study participants (58.1%) were females. The median age of the participants was 20 and almost 42.7% of the participants used in ear media while using the phone. 10.9% and 19.4% showed symptoms of tinnitus and hard of hearing respectively. On testing the participants with pure tone audiometry, around 9.3% had mild hearing loss and 3.9% had moderate hearing loss. Conclusions: The health hazard caused by the mobile phone usage may not be evident for many years. The students are exposed to smart phones frequently and hence periodic screening and health education regarding the harm of using mobile phones for longer duration should be made imperative.